Mind mapping in the Argument Driven Inquiry (ADI) Model to Improve Students' Cognitive Learning Outcomes on Reaction Rate Topic - Mentari Arie Dian Safitri; Endang Budiasih; Siti Marfu’ah (Jurnal Pendidikan Sains, 2020)
Abstract: The purpose of this study was to determine the effect of mind mapping with Argument Driven Inquiry (ADI) model on student’s cognitive learning outcomes (CLO) in the rate of reaction material. This study was a quasi-experimental design with a 2x2 design factorial. The results showed that: (1) there were differences in CLO for students who were learned using ADI-mind mapping and ADI in the rate of reaction material; (2) there were differences in CLO for students with high initial abilities and students who have low initial abilities learned using ADI-mind mapping and ADI in the rate of reaction material; (3) there weren’t an interaction between students initial abilities and learning models towards student’s CLO.Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh mind mapping dalam model Argument Driven Inquiry (ADI) terhadap hasil belajar kognitif (HBK) pada materi Laju Reaksi. Penelitian ini merupakan eksperimen semu dengan rancangan penelitian factorial 2x2 design. Hasil penelitian menunjukkan bahwa: (1) terdapat perbedaan HBK untuk siswa yang dibelajarkan dengan model ADI-mind mapping dan ADI saja; (2) terdapat perbedaan HBK untuk siswa dengan kemampuan awal tinggi dan siswa dengan kemampuan awal rendah yang dibelajarkan dengan model ADI-mind mapping dan ADI saja; (3) tidak terdapat interaksi antara kemampuan awal siswa dengan model pembelajaran terhadap HBK siswa.